The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.17116/jnevro20181182135-39
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the tenoxicam in patients with ankylosing spondylitis

Abstract: BASDAI and ASDAS indices decreased in patients treated with tenoxicam, the AS activity in patients with on-demand NSAID intake did not change. The change of the ineffective long-term NSAID intake in the 'on-demand' basis to permanent drug intake was associated with a rapid (within 4 weeks) decrease in the clinical activity of ankylosing spondylitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We assume that in some cases, the clinical studies were so-called ‘marketing trials’ [ 34 , 35 , 37 ], i.e. they were conducted not to answer a scientific question but to boost sales by publishing articles in professional journals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that in some cases, the clinical studies were so-called ‘marketing trials’ [ 34 , 35 , 37 ], i.e. they were conducted not to answer a scientific question but to boost sales by publishing articles in professional journals.…”
Section: Discussionmentioning
confidence: 99%
“…We sequentially reviewed each publication until 20 articles that met our inclusion criteria were accrued [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. When we replicated the search a few months later, the results in eLIBRARY were different, in that six additional articles that met the inclusion criteria were found; these were also added to our analysis [30][31][32][33][34][35]. Having consulted the eLIBRARY staff, we could not reliably determine the cause of discrepancy in the search results at different times.…”
Section: Methodsmentioning
confidence: 99%
“…81 Eight studies on NSAIDs were included, of which two non-inferiority RCTs in r-axSpA, one at low and one at unclear RoB (Table 2). [82][83][84][85][86][87][88][89] The first study demonstrated non-inferiority of two doses of etoricoxib (60 and 90 mg daily) versus naproxen 1000 mg daily on VAS spinal pain (SMD between etoricoxib 60 mg and 90 mg with naproxen: 0.07 (−0.24, 0.10) and 0.03 (−0.19, 0.26). 82 The second RCT demonstrated the non-inferiority of two doses of celecoxib (400 mg and 200 mg) versus diclofenac 150 mg daily in VAS global pain (SMD not possible to calculate).…”
Section: Efficacy Of Pharmacological Interventions: Non Tsdmardsmentioning
confidence: 99%